Analisis Tantangan Guru Sekolah Dasar Pada Pembelajaran Abad 21 - Shilvy Anggelia; Erva Karimatunisa; Dwi Ratnawati; Hermawan Wahyu Setiadi (Jurnal Ilmiah Literasi Indonesia, 2025)
Primary school teachers play an important role in forming the basis of children's education, but they are often faced with various challenges that can affect the effectiveness and quality of their teaching. This study aims to determine the obstacles and difficulties experienced by teachers during the learning process in class. This research is a descriptive qualitative research using interview method. Descriptive data analysis was used to analyze the challenges faced by elementary school teachers in carrying out their teaching duties. One of the main challenges identified is managing individual differences in students, including learning abilities, learning styles, and support needs. Teachers face difficulty adapting their teaching approach to meet the diverse needs of each student in the class.